Well-being Social Development Model for the Elderly: A Case Study of the Elderly in Ban Mek Mai Phatthana Community, Nong Mek Subdistrict, Na Chueak District, Maha Sarakham Province - Rasri, Warit; Bhutwanakul, Bancha; Chaipranop, Nutjaree; Lawong, Anucha; Makemuengthong, Chomphunut (Interdisciplinary Academic and Research Journal, 2023)
The important question for Thai society today is whether Thailand is prepared to accommodate the changes in the Thai social structure, to enter an aging society, and to deal with various shadowy problems. This research objectives were (1) to study the problems of the elderly in Ban Mek Mai Phatthana Community, Nong Mek Subdistrict, Na Chueak District, Maha Sarakham Province, and (2) to find a model of social development for well-being for the elderly. A case study of the elderly in Ban Mek Mai Phatthana Community, Nong Mek Sub-district, Na Chueak District, Maha Sarakham Province, was qualitative research. A research tool is an interview form with a target group of 85 people from the specific selection. Then take the information gathered from the interview form, and related documents Let's analyze the content. The results of the research revealed that 1) the problem status of the elderly in Ban Mek Mai Phatthana Community, Nong Mek Sub-district, Na Chueak District, Maha Sarakham Province consisted of 1.1) the condition of economic problems; 1.2) the condition of the health problems of the elderly, for example (2) Mental well-being, (3) Intellectual well-being, (4) Social well-being, 3) Environmental problems in the community, and 2) Social well-being development model for the elderly. A case study of the elderly in Ban Mek Mai Phatthana Community, Nong Mek Sub-district, Na Chueak District, Maha Sarakham Province, consisting of 3 patterns: (1) Social welfare provision.